Perceptions of control and unrealistic optimism in early-phase cancer trials. Issue 2 (3rd August 2017) - Jansen, Lynn A; Mahadevan, Daruka; Appelbaum, Paul S; Klein, William M P; Weinstein, Neil D; Mori, Motomi; Degnin, Catherine; Sulmasy, Daniel P
Abstract : Purpose: Recent research has found unrealistic optimism (UO) among patient-subjects in early-phase oncology trials. Our aim was to investigate the cognitive and motivational factors that evoke this bias in this context. We expected perceptions of control to be a strong correlate of unrealistic optimism. Methods: A study of patient-subjects enrolled in early-phase oncology trials was conducted at two sites in the USA. Respondents completed questionnaires designed to assess unrealistic optimism and several risk attribute variables that have been found to evoke the bias in other contexts. Results: One hundred and seventy-one patient-subjects agreed to be interviewed for our study. Significant levels of perceived controllability were found with respect to all nine research-related questions. Perceptions of control were found to predict unrealistic optimism. Two other risk attribute variables, awareness of indicators (p=0.024) and mental image (p=0.022), were correlated with unrealistic optimism. However, in multivariate regression analysis, awareness and mental image dropped out of the model and perceived controllability was the only factor independently associated with unrealistic optimism (p<0.0001). Conclusion: Patient-subjects reported that they can, at least partially, control the benefits they receive from participating in an early-phase oncology trial. This sense of control may underlie unrealistic optimism about benefiting personally from trial participation. Effective interventions to counteract unrealistic optimism may need to address the psychological factors that give rise to distorted risk/benefit processing.